Policy Content Analysis in Minister of Health Regulation Number 15 of 2016 about Hajj Health Istithaah - Idris, Salman Mauluddin; Nurwahyuni, Atik (UI Scholars Hub, 2024)
Indonesia has the world's largest Muslim population and sends the most pilgrims to Saudi Arabia. The Hajj Health Istithaah Policy in Minister of Health Regulation Number 15 of 2016 is the government's effort to carry out health screening for pilgrims before leaving so that they can perform the Hajj in a healthy and independent condition. This research was conducted using a qualitative approach by collecting data through in-depth interviews and document reviews. In this study, Walt and Gilson's Policy Triangle Model was used as a reference for reviewing the Hajj health istithaah policy, especially in the content section of the document and its implementation. The aspects reviewed are the harmonization and relevance of policy content and implementing regulations for the Hajj pilgrimage. Monitoring and evaluation are carried out to monitor the progress and development of policies. Revisions and simplifications of the substance of the policy based on the results of discussions and suggestions from stakeholders are used as input to make improvements to the content of the Hajj health istithaah policy. The conclusion of the review results shows that the policy has been implemented correctly from the center to the regions; research recommendations need revision and simplification of the substance of the Hajj Health Istithaah Policy, as well as other efforts so that pilgrims can achieve health istithaah conditions before leaving to perform the pilgrimage in Saudi Arabia.